1999
DOI: 10.1126/science.284.5418.1354
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Inhibition of Estrogen Receptor Signaling in Transfected Cells

Abstract: Mutations of the breast cancer susceptibility gene BRCA1 confer increased risk for breast, ovarian, and prostatic cancers, but it is not clear why the mutations are associated with these particular tumor types. In transient transfection assays, BRCA1 was found to inhibit signaling by the ligand-activated estrogen receptor (ER-alpha) through the estrogen-responsive enhancer element and to block the transcriptional activation function AF-2 of ER-alpha. These results raise the possibility that wild-type BRCA1 sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
334
2
4

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 450 publications
(356 citation statements)
references
References 20 publications
16
334
2
4
Order By: Relevance
“…Rescue of the inhibition of ER-a by I3C and/or genistein is consistent with previous studies showing that wtBRCA1 inhibits ER-a signalling and a DN-BRCA1 rescues the inhibition (Fan et al, 1999b;2001a, b). However, the finding that BRCA1-siRNA stimulates AR activity and partially reverses the inhibition of DHT-induced AR activity by I3C and genistein is somewhat surprising, since wtBRCA1 and wtBRCA2 were reported to stimulate AR signalling (Yeh et al, 2000;Shin and Verma, 2003).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Rescue of the inhibition of ER-a by I3C and/or genistein is consistent with previous studies showing that wtBRCA1 inhibits ER-a signalling and a DN-BRCA1 rescues the inhibition (Fan et al, 1999b;2001a, b). However, the finding that BRCA1-siRNA stimulates AR activity and partially reverses the inhibition of DHT-induced AR activity by I3C and genistein is somewhat surprising, since wtBRCA1 and wtBRCA2 were reported to stimulate AR signalling (Yeh et al, 2000;Shin and Verma, 2003).…”
Section: Discussionsupporting
confidence: 91%
“…To express BRCA2, a full-length human BRCA2 cDNA (provided by Dr Qingshen Gao, New England Medical Center, Boston, MA, USA) was cloned into the pCMV-Tag2B vector (Stratagene). The human ER-a expression vector and the oestrogen-responsive reporter ERE-TK-Luc were described before (Fan et al, 1999b(Fan et al, , 2001a. Wild-type AR expression vector pSG5-AR and the androgen-responsive reporter plasmid ARE-TK-Luc were provided by Dr Chawshang Chang (University of Rochester, Rochester, NY, USA).…”
Section: Expression Vectors and Reporter Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1999, we reported that BRCA1 inhibits the transcriptional activity of ER-a, the major estrogen receptor in breast epithelial cells (Fan et al, 1999a). This inhibition was selective, since BRCA1 failed to inhibit the activities of other sequence-specific transcription factors, including Sp1, E2F-1, c-Fos, and c-Jun.…”
Section: Regulation Of Transcriptionmentioning
confidence: 99%
“…A number of investigations performed in cultured cells revealed that BRCA1 specifically inhibits estrogen/ERa transcription activation in either estrogen-dependent (Fan et al, 1999) or estrogenindependent ways (Zheng et al, 2001). It was reported recently that BRCA1 inhibits estrogen biosynthesis through modulating aromatase expression in ovarian granulosa cells (Hu et al, 2005).…”
Section: Introductionmentioning
confidence: 99%